Enhancement of penetration field in vortex matter in mesoscopic superconductors due to Andreev bound states - Dolz, M.I.; Bolecek, N.R.C.; Puig, J.; Pastoriza, H.; Nieva, G.; Guimpel, J.; van der Beek, C.J.; Konczykowski, M.; Fasano, Y.; Fasano, Yanina; Puig, Joaquín; Guimpel, Julio; et al. (American Physical Society, 2019)
Fil: Bolecek, N.R.C. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina